Yerba mate: An overview of physiological effects in humans. (November 2017) - Riachi, Liza Ghassan; De Maria, Carlos Alberto Bastos
Highlights: Antioxidant enzymatic complex was positively modulated. Antilipemic activity was more consistent than glycaemic control. Maté consumption had no effect on anti-glycation. Maté showed potential to increase energy expenditure and weight loss. Carcinogenicity is related to consumption temperature, rather than maté itself. Abstract: This review aims to make an outline of the existing clinical studies from the past twenty years concerning to maté effects in human health. Physiological effects have been attributed to phenolics, methylxanthines and saponins. Antilipemic activity was more consistent than glycaemic control. Maté seems to protect low-density lipoprotein cholesterol (LDL-c) from oxidation in whole plasma. Results from isolated LDL-c particles are contradictory. The antioxidant enzymatic complex was positively modulated, indicating that maté might help in the redox homeostasis maintenance. Most clinical trials did not find a significant positive effect of maté consumption on glycaemia. However, it seems that maté hypoglycaemic effect is more evident in type-2 diabetes mellitus subjects. Maté had no effect on anti-glycation in vivo . It has shown potential to increase energy expenditure and weight loss. Carcinogenicity is related to consumption temperature, not maté itself. Long-term randomized double-blind placebo-controlled studies are essential to provide more consistent data.